From Pigeons to News Portals : Foreign Reporting and the Challenge of New Technology - Hamilton, John Maxwell; Perlmutter, David D., 1962- (Book collections on Project MUSE., 2007)
Ever since the invention of the telegraph, journalists have sought to remove the barriers of time and space. Today, we readily accept that reporters can jet quickly to a distant location and broadcast instantly from a satellite-connected, video-enabled cell phone hanging from their belts. But now that live news coverage is possible from virtually anywhere, is foreign correspondence better? And what are the implications of recent changes in journalistic technology for policy makers and their constituents?. In From Pigeons to News Portals, edited by David D. Perlmutter and John Maxwell Hamilton.